Investigating Male and Female Teachers' Perceptions of Character Education in High school Islamic Studies Curricula in Saudi Arabia - Alwadai, Mesfer Ahmed Mesfer; Alhaj, Ali Albashir Mohammed (Technium Social Sciences Journal, 2023)
The present study scrutinizes the perception of male and female Teachers of character education in high school Islamic studies curricula. The main objectives of the present study are to explore the Islamic studies high school male and female teachers' perceptions of character education in Islamic studies textbooks and analyze Islamic studies high school male and female teachers' opinions on character education and how can be gained through the content of the curricula. The study's central question is what are the Islamic studies high school male and female teachers' perceptions of character education in Islamic studies textbooks?The results of this study are expected to fill the dearth of knowledge about how male and female teachers perceive character education in high school Islamic studies curricula in Arabs contexts in general and in Saudi high school contexts in particular. High school Islamic studies male and female teachers' perceptions of character education in high school Islamic studies curricula were scrutinized by using a five Likert-type questionnaire of twenty items which were assayed quantitatively utilizing descriptive data. The participants of the study were a hundred high school Islamic studies male and female teachers in the Asir region. The foremost results of the investigation indicated that responses of high school Islamic studies male and female teachers to the statements in the questionnaire were positive. The study revealed that the use of character education in high school Islamic studies curricula is beneficial. Based on the findings, the study recommended exploring the role of character education in other textbooks on social studies, languages, and the like.